Age‐related changes of hyoid bone position in healthy older adults with aspiration. (13th November 2013) - Feng, Xin; Todd, Tee; Hu, Yunping; Lintzenich, Catherine R.; Carr, J. Jeffrey; Browne, James D.; Kritchevsky, Stephen B.; Butler, Susan G.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Aspiration, the passage of a bolus below the vocal folds, increases morbidity and mortality in the elderly by increasing the risk of aspiration pneumonia and other conditions. We hypothesized that altered position of the hyoid bone associated with aging may negatively affect airway protection during swallowing (i.e., aspiration) in older adults. Study Design Retrospective study. Methods We re‐reviewed computed tomography (CT) scans of the head from 40 older adults (65–80 years old), comprised of 20 aspirators and 20 nonaspirators, obtained from a previous cohort study. In addition, CT scans of the head from 40 young adults (20–40 years old) were retrieved from a medical records database. Three‐dimensional reconstruction and 2‐dimensional sagittal views were used to measure the distance between the mandible and hyoid bone. Comparisons between age groups, genders, and aspiration status were made. Results Older adults had a larger distance between the hyoid and mandible in both latitude and longitudinal positions compared to the young adults. Among older males, there was evidence that the hyoid bone in the aspirators tended to be positioned more posterior compared to the nonaspirators. Conclusions The distance between the hyoid and mandible is increased with aging, and a more posterior position of the hyoid bone is correlated with aspiration in older males. These findings suggest that age‐related changes in hyoid bone position may be a component of decreased swallowing safety and aspiration in older adults and warrant further investigation. Level of Evidence N/A. Laryngoscope, 124:E231–E236, 2014